Development of prescription-based liquid fertilizer application in the system of rice intensification - Abd Kharim, Muhammad Nurfaiz (2020)
Uniform-based fertilizer application is still being normally used in nutrient management of System of Rice Intensification (SRI) with very less consideration of Precision Farming (PF). The overall study was to develop a precise prescription-based liquid fertilizer formulation for the SRI field by using Unmanned Aerial Vehicle (UAV). The aerial images of the SRI field were captured using a digital camera mounted on a UAV flying at low altitude (< 50 m). The precise amount of nitrogen (N) was then determined by using vegetation indices of IPCA-RGB model and prescribed according to the actual requirement of the rice plant. A laboratory-scale experiment in the greenhouse was performed to establish fertilizer formulation and found that an additional foliar fertilization needs to be conducted during the grain formation stage. A study on the performance of the UAV flying parameters and spraying requirements was performed to establish the operating procedure of aerial fertilizer spraying. Results showed that the droplet pattern and droplet deposition density (59.08 L/min) was higher with a lower coefficient of variations (CV) of droplet uniformity (3.59%) when the UAV flying speed was maintained at 2 m/s and spraying rate of 3.00 L/min at a constant height of 2 m above the rice canopy compared to the higher-flying speeds (4 & 6 m/s) and lower spraying rates (0.75, 1.5, & 2.25 L/min). Twenty plots were set up according to 2 types of liquid fertilizer (organic and inorganic) and 2 methods fertilizer based-rate (uniform and prescription) with 5 replications for each of the treatments. Fertilizer spraying was 5 times during 15 Days After Transplanting (DAT), 35 DAT, 55 DAT, 65 DAT, 75 DAT and harvested at 110 DAT. Aerial image acquisition of the SRI field with the IPCA-RGB model showed a positive result in determining N content for precise fertilizer application. The IPCA-RGB model had a close relationship with SPAD chlorophyll meter in the assessment of chlorophyll content at the rice leaf canopy scale during all the five times fertilization periods. In terms of crop growth and yield performances, results showed that treatment uniform-based rate with inorganic fertilizer had higher plant heights (107.43cm) compared to other treatments. However, the treatment of prescription-based with organic fertilizer showed higher performances for the number of tillers (34a), the number of panicles (19a), and spikelet per hill (46a) compared to other treatments at p = 0.05. Moreover, prescription-based with organic fertilizer treatment showed higher values for yield performances compared to other treatments namely; grain yield (g) (771.35a), net grain yield (g) in 1m2 Crop Cutting Test (CCT) (614.13a), and effective tillers in 1m2 CCT (309a) at p = 0.05. Thus, prescription-based treatment with organic fertilizer shows the lowest moisture content (18.67%) compared to other treatments for the grain moisture comparison. While, for the UAV performance of aerial spraying, treatments that spray prescribed liquid fertilizer had a faster time to complete the spraying cycle and refilling process compared to treatments of uniform- based rate. In terms of cost analysis, prescription-based treatment with organic fertilizer had higher in total revenue (RM 9,405), net profit (RM 3,707.16), and return of investment (ROI) (65.06%) compared to other treatments. However, organic-based treatment either for uniform (RM 5,714.38) or prescription-based (RM 5,697.84) showed a higher amount of production cost compared to inorganic-based treatment either for uniform (RM 5,669.54) or prescription-based (RM 5,589.04). Overall, a prescription- based fertilizer application was feasible to be applied to the rice plant with better yield performances and saving in fertilizer amounts compared to uniform-based rate treatment. Thus, results from this study can provide technical procedure, and theoretical basis for the application of precise liquid fertilizer through the prescription-based method and usage of UAV for liquid fertilizer spraying within the SRI farming.